THE EXCLUSIVITY OF MUSIC/SONG CREATORS IS GUARANTEED BY COPYRIGHT LAW NUMBER 28 OF 2014 - Rumatiga, Hidayat; Aminulloh, Muhammad; Nurwati; Yumarni, Ani; Devi, Sylvia Haura Carolina; Kelutur, Suparlan (Fakultas Hukum Universitas Djuanda, 2024)
There is a misunderstanding from the user's perspective that musicians are people who need recognition and need money. In fact, musicians really want the exclusivity of musicians guaranteed by law, because the law is biased. In article 9 of the Copyright Law, every use of copyrighted creations that contain commercial use must obtain permission from the creator. Paragraph (3) all people who do not have permission are prohibited from reproducing or obtaining commercial use. This study aims to examine and analyze the exclusive rights of music or song creators guaranteed by law. This study is empirical juridical with sample selection using random sampling and purposive sampling techniques that are adjusted to the selected sample. The data studied include primary data, namely data obtained from information obtained from interviews with related parties from LMK, and secondary data is data that supports information or supports the completeness of primary data, then analyzed descriptively qualitatively. The results of the study indicate that the exclusivity of song/music creators is to obtain moral rights, economic rights and transfer rights. Creators who own creations must obtain benefits from their creations, so if they do not obtain them, legal protection is needed.